Influence of the environment on ragweed pollen and their sensitizing capacity in a mouse model of allergic lung inflammation - Liu, Shu-Hua; Kazemi, Sahar; Karrer, Gerhard; Bellaire, Anke; Weckwerth, Wolfram; Damkjaer, Jakob; Hoffmann, Oskar; Epstein, Michelle M. (Frontiers in Allergy, 2022)
Common ragweed (Ambrosia artemisiifolia) is an invasive plant with allergenic pollen. Due to environmental changes, ragweed pollen (RWP) airborne concentrations are predicted to quadruple in Europe by 2050 and more than double allergic sensitization of Europeans by 2060. We developed an experimental RWP model of allergy in BALB/c mice to evaluate how the number of RWP and how RWP collected from different geographical environments influence disease. We administered RWP six times over 3 weeks intranasally to the mice and then evaluated disease parameters 72 h later or allowed the mice to recover for at least 90 days before rechallenging them with RWP to elicit a disease relapse. Doses over 300 pollen grains induced lung eosinophilia. Higher doses of 3,000 and 30,000 pollen grains increased both eosinophils and neutrophils and induced disease relapses. RWP harvested from diverse geographical regions induced a spectrum of allergic lung disease from mild inflammation to moderate eosinophilic and severe mixed eosinophilic-neutrophilic lung infiltrates. After a recovery period, mice rechallenged with pollen developed a robust disease relapse. We found no correlation between Amb a 1 content, the major immunodominant allergen, endotoxin content, or RWP structure with disease severity. These results demonstrate that there is an environmental impact on RWP with clinical consequences that may underlie the increasing sensitization rates and the severity of pollen-induced disease exacerbation in patients. The multitude of diverse environmental factors governing distinctive patterns of disease induced by RWP remains unclear. Further studies are necessary to elucidate how the environment influences the complex interaction between RWP and human health.